A taxonomic revision of the genus Cleome L. (Capparaceae) in Bangladesh - Ara, Hosne; Khan, Bushra; Mia, Md. Mansur-ul-Kadir (Bangladesh Journal of Plant Taxonomy, 2007)
The available record of the genus Cleome L. for Bangladesh has been updated in this paper and includes C. diffusa, C. gynandra, C. hassleriana, C. rutidosperma and C. viscosa. The updating has been done in case of nomenclature with important synonyms, local names, description of the taxa along with illustrations, flowering and fruiting times, ecological notes, specimens examined and their geographical distribution. For identification of the species, a dichotomous bracketed key has been added in this paper. Information on chromosome number and economic importance have also been provided where available. Key words: Cleome, Taxonomic revision, Capparaceae, Bangladesh DOI: 10.3329/bjpt.v14i1.520 Bangladesh J. Plant Taxon. 14(1): 25-36, 2007 (June)